Keberkahan Baitul Maqdis dan Implementasinya di Era Kontemporer: Telaah Dalam Perspetif Kitab Tafsir Al-Munir - Fajri, Fadhilah Maulida; Siti Rokhani; Murdianto (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study examines the blessing of Baitul Maqdis in the Qur'an using tafsir methodology, particularly through the interpretation given by Wahbah az-Zuhaili in Tafsir al-Munir, as well as the implementation of the meaning of the blessing of Baitul Maqdis in the contemporary context. The analysis focuses on five Qur'anic verses that refer to the “blessed land,” examining the meaning of blessing that includes both material and spiritual dimensions, and emphasizing its historical significance and universal applicability. The results explain that the prosperity of Baitul Maqdis goes beyond agricultural fertility or geographical advantages; it encompasses ethical, spiritual, and mission-oriented values that advocate resistance to colonization and injustice. In contemporary discourse, this blessing is manifested through the role of Baitul Maqdis as a center of global awareness, an inspiration for struggle, a promoter of interfaith solidarity, and a source of spiritual energy that strengthens dedication to upholding justice. This research confirms that understanding the blessing of Baitul Maqdis is an essential element of the Muslim aqidah, which involves the obligation to uphold its sanctity and the profound principles embedded in it.